Attitudes of a geriatric population towards risks about COVID‐19 pandemic: in the context of anxiety and depression. Issue 5 (15th June 2021) - Yurumez Korkmaz, Busra; Gemci, Emine; Cosarderelioglu, Caglar; Yigit, Seher; Atmis, Volkan; Yalcin, Ahmet; Varli, Murat; Aras, Sevgi
Abstract: Background: A curfew for elderly people was announced in Turkey to protect the geriatric population during the COVID‐19 pandemic. Although this may have the beneficial effect of preventing infection, psychological distress may also increase with prolongation of the pandemic. Methods: Geriatric patients were interviewed by telephone due to the ongoing curfew. Demographical characteristics, comorbidities, personal risk perception of COVID‐19, common concerns related to COVID‐19, and experiences of delayed hospital admission due to the pandemic were recorded. The Hospital Anxiety and Depression Scale (HADS) was used to assess psychological distress, anxiety, and depression. Results: Participants ( n = 136; 82 females, 60.3%) had a mean age of 73.4 ± 5.9 years. The most common comorbidity was hypertension (75%). Approximately 80% of the participants reported a decrease in physical activity during the curfew period. The HADS scores indicated rates of anxiety as 25.7% and depression as 16.9%. Anxiety was significantly more common in females than males ( P  = 0.002). Sleep problems ( P  = 0.000), fatigue ( P  = 0.000), and hopelessness ( P  = 0.000) were more common in participants with depression and anxiety. Logistic regression analyses showed an association between a delay in hospital admission and the presence of depression ( P  = 0.0029, R 2  = 0.146). Personal risk perception of COVID‐19 was statistically significantly higher among patients with anxiety ( P  = 0.0027, R 2  = 0.157). Conclusion: Decreased adaptation to external and internal factors among older individuals may facilitate unfavourable outcomes of the pandemic. These results indicate that the geriatric population was mentally and physically affected by the restrictions and isolation.